The Backward Euler Fully Discrete Finite Volume Method for the Problem of Purely Longitudinal Motion of a Homogeneous Bar - Ziwen Jiang; Deren Xie (Abstract and Applied Analysis)
We present a linear backward Euler fully discrete finite volume method for the initial-boundary-value problem of purely longitudinal motion of a homogeneous bar and an give optimal order error estimates in L2 and H1 norms. Furthermore, we obtain the superconvergence error estimate of the generalized projection of the solution u in H1 norm. Numerical experiment illustrates the convergence and stability of this scheme.